2017
DOI: 10.3856/vol43-issue3-fulltext-5
|View full text |Cite
|
Sign up to set email alerts
|

Growth and metabolic response of whiteleg shrimp Litopenaeus vannamei and Nile tilapia Oreochromis niloticus in polyculture fed with potential probiotic microorganisms on different schedules

Abstract: Probiotics and co-culture of shrimp and tilapia are two strategies to improve yield and ecoefficiency of both species. However, only few studies have analyzed the combination of these two strategies. This study analyzes the effect of a mixture of potential probiotics supplied in the diet at different frequencies in a system of shrimp (10/m2) and tilapia (5/m2) in a trial lasting 84 days. The probiotics mixture was composed of four lactic acid bacteria and one yeast strain that were supplied either daily, every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
6
0
2
Order By: Relevance
“…Acylglyceride (AG) levels in the haemolymph of shrimp fed the commercial diet (240 mg dl −1 ) and the L10 diet (180 mg dl −1 ) are much higher than levels from other studies (Apún-Molina et al, 2015;Mercier et al, 2006). This might be partly explained by the acylglyceride content measured including the acylglyceride content of lysed haemocyte cells, as for the other heamolymph metabolites due to sample treatment.…”
Section: Haemolymph Metabolic Parametersmentioning
confidence: 85%
“…Acylglyceride (AG) levels in the haemolymph of shrimp fed the commercial diet (240 mg dl −1 ) and the L10 diet (180 mg dl −1 ) are much higher than levels from other studies (Apún-Molina et al, 2015;Mercier et al, 2006). This might be partly explained by the acylglyceride content measured including the acylglyceride content of lysed haemocyte cells, as for the other heamolymph metabolites due to sample treatment.…”
Section: Haemolymph Metabolic Parametersmentioning
confidence: 85%
“…These eels were fed a paste prepared from a 1:2.2 powdered feed to water ratio. Based on earlier studies (Aisyah et al, 2020;Apún-Molina et al, 2015), a new culture of Bacillus sp. PCP1, Lactococcus sp.…”
Section: In Vivo Application Of Probiotics In Elvermentioning
confidence: 99%
“…freundii, Candida parapsilosis, Pseudomonas spp. (with P. aeruginosa highly represented), Micrococcus luteus, Lactobacillus plantarum, L. fermentum, L. acidophilus, L. brevis, L. rhamnosus, L. lactis, Pediococcus pentosaceus and P. parvulus (Aly et al 2008a;El-Rhman et al 2009;Giri et al 2014;Ap un-Molina et al 2015;Ridha & Azad 2016;Maji et al 2017;Amir et al 2018;Van Doan et al 2018;Xia et al 2018). Giri et al (2014) showed that a mixture of B. subtilis, P. aeruginosa and L. plantarum isolated from the gut of roho labeo enhanced growth, immune response and survival after A. hydrophila challenge in juvenile L. rohita.…”
Section: Probiotic Sources-autochthonous or Allochthonousmentioning
confidence: 99%
“…Similarly, Apún‐Molina et al . (2015) showed that four strains of the LAB, Ped. parvulus and the yeast Candida parapsilosis , all isolated from Nile tilapia intestine, enhanced growth.…”
Section: Probiotic Sources—autochthonous or Allochthonousmentioning
confidence: 99%